Pediatric antiphospholipid syndrome - Madison, Jacqueline A. (Eur J Rheumatol, 2020)
Despite its potential to cause significant morbidity in children, pediatric antiphospholipid syndrome (APS) is an understudied condition. In this review, we will cover what is known about pediatric APS epidemiology and how the clinician might approach the diagnosis of pediatric APS. We will highlight similarities and differences with the adult disease, both for primary APS and in the context of lupus. Clinical manifestations beyond thrombosis, especially neurologic and hematologic in nature, will be discussed. We will also consider what unique implications antiphospholipid antibody-positivity may have for children with lupus and for neonates born to mothers with APS. The approach to treatment will be covered, including the unique impact of APS medications on children as compared with adults. Finally, the importance of future mechanistic research is emphasized as physicians endeavor to provide the personalized care that children with APS clearly deserve.